Potential of e-Fischer Tropsch diesel and oxymethyl-ether (OMEx) as fuels for the dual-mode dual-fuel concept. (1st November 2019) - García, Antonio; Monsalve-Serrano, Javier; Villalta, David; Lago Sari, Rafael; Gordillo Zavaleta, Victor; Gaillard, Patrick
Highlights: The direct replacement of diesel by HVO improves the fuel consumption at low load. HVO and OMEx enable a soot reduction during the difussive dual-fuel operation. The use of OMEx implies larger energizing times, which reduces the engine efficiency. The OMEx produced from wind power substantially reduces the CO2 footprint. Abstract: The dual-mode dual-fuel combustion strategy allows operating over the entire engine map by implementing a diffusive dual-fuel combustion at high engine loads. This requires increasing the amount of exhaust gas recirculation to control the NOx emissions, which penalizes the soot levels. At these conditions, the use of non-sooting fuels as the e-Fischer Tropsch Diesel (e-FT) and oxymethylene dimethyl ethers (OMEx) could be a potential way to avoid the NOx-soot trade-off. The experimental results acquired in a compression ignition multi-cylinder medium-duty engine evidence that the higher oxygen content of OMEx allows reducing the soot emissions at high loads to near zero levels, while e-FT promotes a soot reduction of around 20% as compared to diesel. Nonetheless, the low lower heating value of OMEx leads to excessive injection durations, enlarging the combustion process and increasing the fuel consumption around 1.3–7.2% and 1.4–5.3% as compared to diesel and e-FT, respectively, depending on the engine load. Finally, the well to wheel analysis confirms the potential in reducing the carbon dioxide footprint of OMEx (14.8–69%) and e-FT (0.3–38.5%) compared to diesel, as they can be synthetized via direct air capture as a source of carbon and using renewable energy.